Quantum structure of space and time:Proceedings of the 23rd Solvay conference on physics,Brussels,Belgium,1-3 december,2005 - Quantum structure of space and time; Gross David , ed. (World Scientific, 2007)
These proceedings give a broad overview with unique insight into the most fundamental issues raised by this challenge for 21st century physics, by distinguished renowned scientists. The contributions cover: the status of quantum mechanics, spacetime singularities and breakdown of classical space and time, mathematical structures underlying the most promising attempts under current development, spacetime as an emergent concept, as well as cosmology and the cosmological constant puzzle. A historical overview of the Solvay conferences by historian of sciences Peter Galison opens the volume.
Keywords: Astrophysics; Cosmology; Quantum theory; Space and time